Enhancing Fertility and Genetic Progress in Poultry through Artificial Insemination: Current Trends and Innovations - Meel, Mamta; Jhamb, Dinesh; Bansal, Krishna Nand; Gaur, Mitesh; Meena, Abhay Kumar; Jinagal, Sujata; Kumar, Pradeep (International Journal of Bio-resource and Stress Management, 2025)
Artificial insemination (AI) has transformed poultry reproduction by enabling genetic improvement, enhancing productivity, and addressing challenges such as disease transmission and mating inefficiencies. This method involves manually depositing semen into the female reproductive tract, maximizing the utilization of genetically superior males. AI is particularly valuable in overcoming size disparities in broilers, optimizing mating in specialized breeds, and preserving endangered avian species. Semen is collected using techniques like abdominal massage, gloved-hand methods, and electroejaculation, with abdominal massage being the most widely used for its simplicity and non-invasive nature. Collected semen is evaluated for parameters such as volume, sperm concentration, motility, viability, and genetic integrity. Nutritional interventions and optimal management practices enhance semen quality, while extenders like BPSE improve viability for up to 24 hours at 5°C. Cryopreservation protocols, including the Pellet and Straw methods, enable long-term genetic preservation at -196°C, while tailored thawing protocols restore sperm functionality for effective use in AI. Timely insemination, typically after oviposition, minimizes oviduct obstructions and increases fertility rates, with doses of 100–500 million sperm cells session-1 ensuring high success rates. Technological advancements, including cryopreservation, genomic selection, and automation, have further improved AI’s efficacy. Despite challenges such as storage-induced sperm damage and ethical concerns, AI remains indispensable for sustainable poultry reproduction, significantly contributing to genetic diversity, enhanced productivity, and global food security through the integration of advanced technologies and sustainable practices.